Assessment of Particulate Matter (PM\(_10\)) using Chemistry Transport Modeling in Agadir City, Morocco - Ajdour, Amine; Leghrib, Radouane; Chaoufi, Jamal; Fetmaoui, Hassan; Bousseta, Mohamed; Chirmata, Ahmed (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
According to the World Health Organization (WHO), the effects of outdoor and indoor air pollution result in approximately 7 million early deaths each year. In Morocco’s case, the economic cost of air quality degradation is about 1.62 percent of GDP. Also, several studies reported the significant influence of local meteorological factors on the PM\(_10\) daily concentration during the synoptic climate conditions and cyclonic circulation. In this sense, Agadir city is a coastal city, and its proximity to the desert makes it very exposed to particles. Accordingly, this study allows, on one hand, to evaluate the performance and to understand the limitations of the WRF-CHIMERE modeling system used to simulate the maximum concentrations of PM\(_10\) in the city of Agadir, based on observations made in spring and summer 2010. On another hand, in order to better understand the situation, the impact of meteorological variables and anthropogenic emissions on PM\(_10\) is being investigated. The preliminary results of air quality modeling pointed out some PM\(_10\) dispersion issues in the area of Agadir. In particular, the results highlighted the influence of temperature and wind speed, which were correlated with PM\(_10\) concentration. Besides, CHIMERE simulations suggested that anthropogenic emissions control is essential to reduce PM\(_10\) by up to 15%. The PM\(_10\) underestimation is attributed to the meteorological observation/model discrepancy and the effect of emissions. The results underline the importance of meteorology on PM\(_10\) dispersion and have significant policy considerations for Moroccan air quality strategy.